Photo-Voltaic based Smart Irrigation Cart. (April 2020) - Anand, A.; Banshwar, A.; Sharma, N. K.; Sharma, B. B.; Pathak, M.
Abstract: The need of energy is increasing dramatically in all sectors of life. The cost-effective solution be the answer for all our energy requirements. Renewable energy is the best possible solution to replace conventional energy sources, both in terms of cost and environmental issues. While considering Indian farming system, electricity is a source of problem behind fruitful irrigation of the land. PV based smart irrigation cart can the solution for electricity problems faced by Indian farming where there is no electricity. The proposed approach consists of PV powered water pump system installed on a mobile cart for irrigating the field. The present work is based on the concept of "pay for power" where an independent source of power will be developed and utilized by the farmers for their irrigation purpose. It will also reduce the dependency of the farmers on conventional electrical companies and further reduces the cost of farming.